On the Issue of Automotive Paint Technology and Composition of Paints and Varnishes Used - L. I. Modinova (Теория и практика судебной экспертизы)
Information on some vehicles dyeing technologies produced in Gorky Automobile Plant is presented, experimental infrared spectra of enamels and primer paints used for their dyeing are obtained.